Explaining the rapid emergence of battery-rickshaws in New Delhi: Supply-demand, regulation and political mobilisation. (September 2017) - Harding, Simon; Kandlikar, Milind
Highlights: Battery-rickshaws have spread rapidly in New Delhi despite the absence of state backing. They perform a niche role in the city's urban transport system, namely "last mile" trips. They have taken this market from cycle-rickshaws. Formalisation on concessionary terms occurred due to political factors. Abstract: Many Indian cities are investing in mass transit projects, such as metro rail networks and bus rapid transit (BRT) systems. In addition to mass transit, the development of an effective public transport network also requires the integration of many thousands of local paratransit operators who provide mobility in areas poorly served by the formal public transport system. In New Delhi battery rickshaws have emerged as one such mode in a dramatic way. In 2010, there were no battery rickshaws, but by 2013, there were an estimated 100, 000, operated primarily by individual owner-drivers. This proliferation came despite a complete absence of state involvement: battery-rickshaws operated outside the ambit of the regulation, and in defiance of the city's very highly regulated paratransit market. This paper aims to identify the causal factors behind their emergence, spread and eventual formalisation based on fieldwork carried out in New Delhi in 2014–2015. In doing this it makes arguments about their role and political-economy. It uses survey data to show that battery-rickshaws provide "last mile connectivity" to metro stations, a market in which they are out-competing all other modes including low-cost cycle-rickshaws. It argues that the demographic advantages enjoyed by battery-rickshaw operators enabled their constitution as a voting bloc in the Delhi Legislative election in 2014, which effectively guaranteed formalisation on concessionary terms. Regulators must consider the role of paratransit as an employer, rather than focusing on legality, as they seek to meet the rising demand for last-mile services in urban areas of the developing world.